A Review of the McMorran Diet for Rearing Lepidoptera Species With Addition of a Further 39 Species. Issue 1 (5th February 2016) - Hervet, V. A. D.; Laird, R. A.; Floate, K. D.
Abstract: Research on cutworms led us to explore the use of the McMorran diet to rear lepidopteran species, mainly Noctuidae, under laboratory conditions. We documented the development of 103 lepidopteran species, including 39 species not previously reported in the literature, to be reared on this diet. Given its low cost, ease of preparation, and wide species' acceptance, this diet provides a powerful tool for facilitating Lepidoptera and other insects rearing and research in the laboratory. Résumé Une recherche sur les noctuelles nous a permis d'élever des larves de nombreuses espèces de lépidoptères, principalement des noctuelles, sur un substrat artificiel du nom de «McMorran diet» en laboratoire. Nous reportons le développement de 103 espèces de lépidoptères, dont 39 espèces qui n'ont pas encore été documentées, comme pouvant se développer sur ce substrat artificiel. Étant donné son faible coût, facilité de préparation, et large champ d'action, ce substrat artificiel peut grandement faciliter la recherche sur les lépidoptères et autres insectes en laboratoire.